2008
DOI: 10.1016/j.jfineco.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Trading imbalances, predictable reversals, and cross-stock price pressure

Abstract: We test the implications of a multi-asset equilibrium model in which a finite number of risk-averse liquidity providers accommodate non-informational trading imbalances. These imbalances generate predictable reversals in stock returns. An imbalance in one stock also affects the prices of other stocks. The magnitude of the cross-stock price pressure depends on the correlations of the stocks' underlying cash flows. The model implies that non-informational trading increases the volatility of stock returns. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(63 citation statements)
references
References 48 publications
3
60
0
Order By: Relevance
“…A common thread in these theories is that shocks to prices are accompanied by shocks to liquidity and/or trading activity. For example, price shocks can arise because financial intermediaries reduce the supply of liquidity in the face of funding constraints (e.g., Gromb and Vayanos, 2002;Brunnermeier and Pedersen, 2009) or because of a surge in the demand for liquidity when wealth effects, loss limits, or hedging desires induce traders to sell (e.g., Kyle and Xiong, 2001;Morris and Shin, 2004;Andrade, Chang, and Seasholes, 2008).…”
Section: Coinciding Jumps In Prices Liquidity and Trading Activity mentioning
confidence: 99%
See 1 more Smart Citation
“…A common thread in these theories is that shocks to prices are accompanied by shocks to liquidity and/or trading activity. For example, price shocks can arise because financial intermediaries reduce the supply of liquidity in the face of funding constraints (e.g., Gromb and Vayanos, 2002;Brunnermeier and Pedersen, 2009) or because of a surge in the demand for liquidity when wealth effects, loss limits, or hedging desires induce traders to sell (e.g., Kyle and Xiong, 2001;Morris and Shin, 2004;Andrade, Chang, and Seasholes, 2008).…”
Section: Coinciding Jumps In Prices Liquidity and Trading Activity mentioning
confidence: 99%
“…2 Recent theoretical studies on such liquidity channels include Kyle and Xiong (2001), Gromb and Vayanos (2002), Kodres and Pritsker (2002), Bernardo and Welch (2004), Morris and Shin (2004), Yuan (2005); Gârleanu and Pedersen (2007), Pasquariello (2007), Andrade, Chang, and Seasholes (2008), Brunnermeier and Pedersen (2009), Huang and Wang (2009), and Cespa and Foucault (2014).…”
mentioning
confidence: 99%
“…Extensive empirical studies have demonstrated that non-informational trading affects stock prices and returns 1 . Many of them have further shown that noninformational trading can lead to certain predictable patterns of stock returns or can forecast future stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…Many of them have further shown that noninformational trading can lead to certain predictable patterns of stock returns or can forecast future stock returns. [9] documents positive excess returns in the month following intense buying by individuals and negative excess returns after 1 individuals sell. They suggest that the documented patterns are consistent with the notion that risk-averse individuals provide liquidity to meet institutional demand for immediacy.…”
Section: Introductionmentioning
confidence: 99%
“…In asymmetric information models based on Kyle (1985), private information on liquidity-motivated demand allows speculators to better infer the value of fundamentals (e.g., Fishman and Longstaff 1992 ; Madrigal, 1996), to trade on their own account and front-run their clients been documented for other exchanges. 5 The role of liquidity provision when markets open is thus a hotly debated question. My paper shows that the revelation of non-fundamental information is a way for dealers to better manage their inventory exposure.…”
mentioning
confidence: 99%